Fault‐tolerant control design to enhance damping of inter‐area oscillations in power grids. (20th March 2013) - Segundo Sevilla, F. R.; Jaimoukha, I.; Chaudhuri, B.; Korba, P.; Odgaard, P. F.; Aubrun, C.; Majanne, Y.
SUMMARY In this paper, passive and active approaches for the design of fault‐tolerant controllers (FTCs) are presented. The FTCs are used to improve the damping of inter‐area oscillations in a power grid. The effectiveness of using a combination of local and remote (wide area) feedback signals is first demonstrated. The challenge is then to guarantee a minimum level of dynamic performance following a loss of remote signals. The designs are based on regional pole placement using linear matrix inequalities. First, a passive FTC is proposed. It is shown that the computation of the controller reduces to the solution of bilinear matrix inequalities. An iterative procedure is then used to design the controller. Next, as an alternative to active, time‐varying controllers, one for each fault scenario, we propose an approach for the design of a 'minimal switching' FTC in which only one controller is designed, but where a simple switch is incorporated into the controller structure. A case study in a linear and nonlinear Nordic equivalent system is presented to show that the closed‐loop response using a conventional control design could deteriorate the performance or even destabilize the system if the remote signals are lost and to demonstrate the effectiveness of the proposed FTC designs. Copyright © 2013 John Wiley & Sons, Ltd.